2016
DOI: 10.1038/nn.4287
|View full text |Cite
|
Sign up to set email alerts
|

Reward and choice encoding in terminals of midbrain dopamine neurons depends on striatal target

Abstract: Dopaminergic (DA) neurons in the midbrain provide rich, topographic innervation of the striatum and are central to learning and to generating actions. Despite the importance of this DA innervation, it remains unclear if and how DA neurons are specialized based on the location of their striatal target. Thus, we sought to compare the function of subpopulations of DA neurons that target distinct striatal subregions in the context of an instrumental reversal learning task. We identified key differences in the enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

65
371
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(437 citation statements)
references
References 52 publications
65
371
1
Order By: Relevance
“…Considering the role of DA neuron burst firing in reward prediction error coding (Schultz et al, 1997; Glimcher, 2011), the observed effects of the mutation are to an extent unexpected, as no significant changes in learning rates were observed. Still, we note that the reduced win-stay probability is actually similar to the effect reported in the case of optogenetic studies, where the inhibition of DA neurons imitating negative reward prediction error reduced the likelihood of returning to the previously rewarded alternative (Hamid et al, 2016; Parker et al, 2016). Moreover, the study by Pessiglione et al (2006) offers a possible explanation for why the reduced bursting of DA neurons might have led to less deterministic behavior rather than a reduced learning rate.…”
Section: Discussionsupporting
confidence: 84%
“…Considering the role of DA neuron burst firing in reward prediction error coding (Schultz et al, 1997; Glimcher, 2011), the observed effects of the mutation are to an extent unexpected, as no significant changes in learning rates were observed. Still, we note that the reduced win-stay probability is actually similar to the effect reported in the case of optogenetic studies, where the inhibition of DA neurons imitating negative reward prediction error reduced the likelihood of returning to the previously rewarded alternative (Hamid et al, 2016; Parker et al, 2016). Moreover, the study by Pessiglione et al (2006) offers a possible explanation for why the reduced bursting of DA neurons might have led to less deterministic behavior rather than a reduced learning rate.…”
Section: Discussionsupporting
confidence: 84%
“…Although dopaminergic activity cannot be assessed directly using fMRI, both effort and reward PEs were evident in segregated regions of dopaminergic-rich midbrain, and where an effective connectivity analysis indicated a directional influence from SN/VTA toward subcortical (reward PE) and cortical (effort PE) targets via ascending mesolimbic and mesocortical pathways, respectively. Dopaminergic midbrain is thought to comprise several distinct dopaminergic populations that have dissociable functions (54,56,67,68). Here we demonstrate a segregation between effort and reward learning within SN/VTA across the domains of task activation, functional connectivity, and gray matter density.…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine modifies the efficacy of the corticostriatal synapses, as well as the striatal excitability directly, using signals that incorporate both expectation and external gains and losses (3)(4)(5). Decades of research have revealed the manner in which signals relaying information concerning expected and actual gains and costs are incorporated in the striatal dynamic system (6)(7)(8)(9).…”
mentioning
confidence: 99%